2021
DOI: 10.3390/bs11020020
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Anxiety-Induced Sleep Disturbance among in-School Adolescents in Ghana: Evidence from the 2012 Global School-Based Health Survey

Abstract: (1) Background: Psychological problems of adolescents have become a global health and safety concern. Empirical evidence has shown that adolescents experience diverse mental health conditions (e.g., anxiety, depression, and emotional disorders). However, research on anxiety-induced sleep disturbance among in-school adolescents has received less attention, particularly in low- and middle-income countries. This study’s central focus was to examine factors associated with t anxiety-induced sleep disturbance among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…This approach is essential as the literature indicates parents and caregivers easily detect behavioral issues, and therefore collaboration between schools and parents is indispensable [ 7 ]. Other scholars also found a connection between home activities, such as waking up time due to school start period and students’ behavioral issues [ 8 ], and sleep disturbance and behavioral issues with school children [ 27 ]. So, teachers need to plan meaningful and authentic activities to motivate students to engage and learn from them with the active involvement of parents in supervisory roles for their wards.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is essential as the literature indicates parents and caregivers easily detect behavioral issues, and therefore collaboration between schools and parents is indispensable [ 7 ]. Other scholars also found a connection between home activities, such as waking up time due to school start period and students’ behavioral issues [ 8 ], and sleep disturbance and behavioral issues with school children [ 27 ]. So, teachers need to plan meaningful and authentic activities to motivate students to engage and learn from them with the active involvement of parents in supervisory roles for their wards.…”
Section: Discussionmentioning
confidence: 99%
“…For further analysis, this variable was dichotomized into no anxiety-induced sleep disturbance (“never,” “rarely,” and “sometimes”) and anxiety-induced sleep disturbance (“most of time” and “always”). In the absence of a specific cut-off point to determine anxiety-induced sleep disturbance, this choice was based on the categorization made in previous studies ( Vancampfort et al, 2018 ; Smith et al, 2020 ; Werneck et al, 2020 ; Ahinkorah et al, 2021a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, Vancampfort et al (2018) showed that the overall prevalence of anxiety-induced sleep disturbance, defined as being worried about something that keeps you awake at night, was 7.8% in their study involving 181,093 adolescents from 67 countries. Other authors have used a more comprehensive definition of anxiety-induced sleep disturbance, considering it as a condition of low sleep quality, lack of sleep or clinical insomnia as a consequence of loneliness (either social or emotional), worries, sleep disturbance, and disproportionate fear ( Joyce-Beaulieu and Sulkowski, 2016 ; Ahinkorah et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%